Media Pembelajaran Bina Diri Anak Tunagrahita Sdlb Negeri Bekasi Jaya Berbasis Android - Aida Fitriyani; Hendarman Lubis; Andi Achmad (Fakultas Ilmu Komputer dan Desain - Unsurya, 2023)
Self-Development is a special subject in Special Schools (SLB). However, until now the Self Development subject has not utilized smartphone technology, with the need for new innovations so that mentally retarded children are interested in carrying out self-development activities, namely by utilizing Android-based smartphone technology to make it easier for students, teachers, and parents in helping the learning process of students who are more flexible in its use because it is easy to get and download in the play store. Therefore, an Android-based learning application was built to make it easier for teachers and parents. In the process of making this application, the software used is Android Studio which uses the Java programming language, as well as for application display design using Adobe Premiere Pro and Corel draw software. And for the software development method used is Model Rapid Application Development (RAD). For application testing carried out using Blackbox. The result of this research is to make the teaching and learning process of students easier and more interesting